2022
DOI: 10.1186/s13104-022-05985-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal intravenous hydration on amniotic fluid index in oligohydramnios

Abstract: Objective Assessing amniotic fluid determines an important dimension of fetal health. Significant relationships of oligohydramnios, which occurs in 1–2% of pregnancies, with abnormal pregnancy outcomes such as intrauterine growth retardation (IUGR), fetal anomalies, umbilical cord compression, fetal distress, preterm childbirth, meconium-stained amniotic fluid, perinatal mortality and cesarean section necessitate the measurement of amniotic fluid volume in many prenatal fetal health assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…14% of the studied group were workers, only 4% were smokers, 60% of the studied group had previous C.S and the other 40% had normal delivery. Table (3) showed that the mean amniotic fluid index was 3.18 ± 1.11, while there was 6% of studied eases had abnormal umbilical artery Doppler.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…14% of the studied group were workers, only 4% were smokers, 60% of the studied group had previous C.S and the other 40% had normal delivery. Table (3) showed that the mean amniotic fluid index was 3.18 ± 1.11, while there was 6% of studied eases had abnormal umbilical artery Doppler.…”
Section: Resultsmentioning
confidence: 93%
“…It may result in cord compression, foetal pulmonary hypoplasia, foetal growth restriction, a low Apgar score, admission to the neonatal intensive care unit (NICU), and foetal mortality. Obstetric problems can include labour that is protracted because of inertia and a higher frequency of surgical interventions (3) . The objective of the present study was to describe the association between oligohydramnios and placental pathology and analyse the effect of oligohydramnios with placental pathology on fetal growth during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Azarkish et al (1) wanted to see how much of an impact intravenous (IV) hydration had on the amniotic fluid index in cases of oligohydramnios. An overall sample size of 61 women (31 in the experimental group and 30 in the placebo group) participated in the research.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal movement is encouraged, which aids in the growth of the skeleton and muscles. It protects the fetus from vascular and nutritional damage by preventing umbilical cord and placental compression (1) .…”
Section: Introductionmentioning
confidence: 99%
“…The initial AFI scores in the IV amino acid and IV hydration groups at the time of admission were comparable in both groups (p = 0.91; NS). Azarkish et al had 4.49 ± 0.34 cm AFI when administering IV amino acids [ 14 ]. Qureshi FU et al had a similar mean AFI at the time of pre-infusion, 4.7 ± 1.58 cm [ 15 ].…”
Section: Discussionmentioning
confidence: 99%